Lao Jiu: the ninth born - Chee, Sek Thim *; Leow, Puay Tin * (Sunway University Department of Performance and Media, 2007)
"The play is about Lao Jiu, the ninth-born child and only son of the Chng family. Lao Jiu is the darling of his family not only because he is the long-awaited youngest son, but also because he is intelligent and obedient.